2023
DOI: 10.3390/ijerph20043563
|View full text |Cite
|
Sign up to set email alerts
|

Benign Paroxysmal Positional Vertigo Is Associated with an Increased Risk for Migraine Diagnosis: A Nationwide Population-Based Cohort Study

Abstract: Previous studies reported an increased risk of benign paroxysmal positional vertigo (BPPV) in patients with migraine. Hence, we aimed to assess the risk of migraine in patients with BPPV. This cohort study was conducted using the Taiwan National Health Insurance Research Database. The BPPV cohort consisted of patients aged <45 years with a diagnosis of BPPV between 2000 and 2009. An age- and sex-matched comparison group free from a history of BPPV or migraine was selected. All cases were followed up from 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Furthermore, a large cohort study from Taiwan reported that BPPV has a higher risk of a migraine diagnosis [30]. A recent study from Italy reported that migraine is one of the risk factors for the recurrence of BPPV following successful canalith repositioning procedures (CRPs) [31].…”
Section: • Causesmentioning
confidence: 99%
“…Furthermore, a large cohort study from Taiwan reported that BPPV has a higher risk of a migraine diagnosis [30]. A recent study from Italy reported that migraine is one of the risk factors for the recurrence of BPPV following successful canalith repositioning procedures (CRPs) [31].…”
Section: • Causesmentioning
confidence: 99%